Perkembangan Sosial Masyarakat Pada Masa Penjajahan - Toni Nasution (Yayasan Azzuhri Lengkok Lombok Timur, 2023)
The social development of society during the colonial period in various countries can bevary depending on the historical, political and social context of each country.But in general, colonization can have a negative impact on social developmentthe people below. In Indonesia, for example, the Dutch colonization lasted for almost three yearscentury has resulted in various social changes in Indonesian society.During the colonial period, the Dutch had introduced a segregating caste systemIndonesian society into several groups based on race, religion, and statussocial. This caste system has created huge social gaps between people Indonesian natives and people of Dutch or Dutch descent. Before the Dutch controlled Indonesia, there had been exploration the oceans in the context of ancient imperialism and colonialism to the archipelago. Portugal and Spain are two pioneering and enthusiastic countriesin exploring the ocean. So as to prevent that from happeningunfair competition between the two countries, on the initiative of Pope Alexander VI,ruler of the Catholic Religion in the Vatican, felt the need to arrange an expeditionoceans in two countries where the majority of the population is Catholic